Detecting unseen falls from wearable devices using channel-wise ensemble of autoencoders. (30th November 2017) - Khan, Shehroz S.; Taati, Babak
Highlights: Investigated the use of Autoencoders to learn generic features from wearable devices. Proposed channel-wise ensemble approaches for Autoencoders to identify unseen falls. Developed new threshold tightening approaches on reconstruction error of Autoencoder. Demonstrated better performance on two fall recognition datasets. Abstract: A fall is an abnormal activity that occurs rarely, so it is hard to collect real data for falls. It is, therefore, difficult to use supervised learning methods to automatically detect falls. Another challenge in automatically detecting falls is the choice of engineered features. In this paper, we formulate fall detection as an anomaly detection problem and propose to use an ensemble of autoencoders to learn features from different channels of wearable sensor data trained only on normal activities. We show that the traditional approach of choosing a threshold as the maximum of the reconstruction error on the training normal data is not the right way to identify unseen falls. We propose two methods for automatic tightening of reconstruction error from only the normal activities for better identification of unseen falls. We present our results on two activity recognition datasets and show the efficacy of our proposed method against traditional autoencoder models and two standard one-class classification methods.